Faktor Faktor Yang Mempengaruhi Kualitas Hidup Pada Pasien TB/HIV - Indawati, Eli; Irawati, Winda (Universitas Malahayati, 2025)
ABSTRACT Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) are two global health problems that are interconnected and have a significant impact on the quality of life of sufferers. TB-HIV coinfection is one of the main challenges in the field of public health, especially in developing countries, including Indonesia. To identify factors that influence quality of life in TB-HIV patients. The type of research used is quantitative research and the design used is